Hegemoni dalam Novel "Imarah Ya'qubiyan" Karya 'Ala Al Aswany - wanto, Apri (CAKRAWALA LINGUISTA, 2023)
This study aims to discuss the level of hegemony and the use of hegemony by the authorities in the novel Imarah Ya'qubian. The research data is the novel Imarah Ya'qubian by Ala Al Aswany. Data collection was carried out by means of literature studies and analytical techniques. Data analysis techniques included identification, classification, and analysis in accordance with the theory put forward by Antonio Gramsci. This research method, namely descriptive qualitative approach and Antonio Gramsci's theory of hegemony. The object of research is the novel Imarah Ya'qoubiyan. The results of the study show that at the level of hegemony, integral hegemony is found in 68 data; hegemony declined 22 data; and minimum hegemony of 23 data. This indicates that the designation of Egyptian social strata in the novel Imarah Ya'qoubiyan tends to eliminate dictatorial and despotic intervention. This is evident from the dominance of constructive consensus power, hegemony was successfully created by diplomatic acceptance because there is a mutual relationship. Utilization of hegemony by the dominant class, found for the benefit of social class with a quantity of 53 data; economic interests 26 data; political interests 19 data; and ideological interests 15 data.